2008
DOI: 10.3892/mmr_00000067
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for the local recurrence of hepatocellular carcinoma after single-session percutaneous radiofrequency ablation with a single electrode insertion

Abstract: Abstract. Radiofrequency ablation (RFA) is a new local therapy for hepatocellular carcinoma (HCC). In this study, we investigated the risk factors associated with local recurrence of HCC after single-session RFA with a single electrode insertion. From April 2003 to December 2007, we treated 138 HCC lesions by single-session RFA with a single electrode insertion using the Cool-tip RFA, RTC 2000 and RTC 3000 Systems. Risk factors for the local recurrence of these lesions and complications after RFA were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…For the study that only provided the detailed data about RFA on OS and DFS we used only the relevant information in our meta-analysis [19]. Among the 15 studies, one was performed in China [7], one in Korea [6], twelve in Japan [8]–[10], [17][24], [26] and one in America [25]; three prospective studies [9], [21], [23], five retrospective studies [8], [17], [18], [24], [25], and seven included studies in which study design was not reported clearly. The basic feature description of the studies was summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…For the study that only provided the detailed data about RFA on OS and DFS we used only the relevant information in our meta-analysis [19]. Among the 15 studies, one was performed in China [7], one in Korea [6], twelve in Japan [8]–[10], [17][24], [26] and one in America [25]; three prospective studies [9], [21], [23], five retrospective studies [8], [17], [18], [24], [25], and seven included studies in which study design was not reported clearly. The basic feature description of the studies was summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…23,28,29 However, some hypervascular lesions may be imaged as hypovascular by dynamic CT due to various factors including the timing of imaging, cardiac output, and portal hemodynamics. Disadvantages of dynamic CT include radiation exposure and the risk of allergy to iodine.…”
Section: Discussionmentioning
confidence: 99%
“…23 RFA systems used in this study were the RTC 2000 and 3000 Systems (Boston Scientific Inc., Natick, MA) and the Cool-tip RFA System (Covidien, Boulder, CO). All patients underwent USguided RFA.…”
Section: Rfa Methodsmentioning
confidence: 99%
“…In the previous reports, these factors are also important factors in determining recurrence of HCC after treatment, including RFA. For tumor local recurrence after RFA treatment, tumor size >2.5 cm and tumor size are identified as the main risk factor in Lam's study and Shiozawa's study, respectively [27,28]. Regarding to the recurrence after long term follow-up, tumor with diameter bigger than 3 cm, located near the intrahepatic blood vessels, sub-capsular locations and prothrombin time more than 3 s are independent risk factors in Yang's study [29].…”
Section: Discussionmentioning
confidence: 92%
“…Recently, numerous studies have been proposed for analyzing the risk factors that affect the prognosis after RFA for the patients with HCC [25,[27][28][29]. Different risk factors were identified in different studies and no conclusive results or presumptive predictive models were established.…”
Section: Introductionmentioning
confidence: 99%